1996
DOI: 10.3168/jds.s0022-0302(96)76520-7
|View full text |Cite
|
Sign up to set email alerts
|

Intake, Site, and Extent of Nutrient Digestion of Lactating Cows Grazing Pasture

Abstract: The objective of this study was to determine intake and site and extent of nutrient digestion of lactating cows grazing pasture with or without energy supplementation. Four dual-cannulated (rumen and proximal duodenum) cows were randomly assigned to two groups to graze mixed cool season grass legume pasture with either no supplement or with 6.4 kg of cracked corn and mineral mix daily in a switchback design with three 2-wk periods. Markers (Cr2O3 and Co-EDTA) were used to estimate intake, duodenal flow, fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
3
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 23 publications
8
38
3
1
Order By: Relevance
“…It has been shown that fermentable carbohydrate supplementation reduces ruminal N-NH 3 increasing its capture by microorganisms and its subsequent use in protein synthesis (Berzaghi et al, 1996). However, Wiedmeier et al (1992), comparing the effect of molasses and a molasses by-product on digestibility and rumen fermentation in hay-fed cattle, obtained N-NH 3 concentrations similar to those reported in this study without significant differences between treatments.…”
Section: Discussionsupporting
confidence: 80%
“…It has been shown that fermentable carbohydrate supplementation reduces ruminal N-NH 3 increasing its capture by microorganisms and its subsequent use in protein synthesis (Berzaghi et al, 1996). However, Wiedmeier et al (1992), comparing the effect of molasses and a molasses by-product on digestibility and rumen fermentation in hay-fed cattle, obtained N-NH 3 concentrations similar to those reported in this study without significant differences between treatments.…”
Section: Discussionsupporting
confidence: 80%
“…Intake of orchard grass hay while in the dirt lot, approximately 1 kg/d, was not accounted for in this intake estimation. Average estimated DMI was numerically higher in wk 1 of the study (18.6 DIM, and milk yield and composition (2,6). Grain supplementation was slightly higher (7.2 to 7.6 kg/d DM) in the study of Holden et al (6) compared with the present study.…”
Section: Methodscontrasting
confidence: 50%
“…When CSH was regressed against measured herbage DM yields (kg/ha of DM) the equation (Figure 1) was obtained: Alfalfa-orchardgrass was grazed during the last week of June (wk 7) through the third week of July (wk 10) for 3 h each morning. 2 Average nutrient composition of orchardgrass hay during the study. Ether extract, ash, and macro and micro minerals of OG hay were obtained from NRC (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cows consuming only pasture had a NUE of 21.0 ± 6.1% while supplemented grazing cows improved their NUE, storing in the milk 24.6 ± 3.8% of the ingested N, showing a positive effect of CHO supplementation on NUE (Van Vuuren et al, 1993;Berzaghi et al, 1996;Carruthers and Neil, 1997;Robaina et al, 1998;Reis and Combs, 2000;Walker et al, 2001;Bargo et al, 2002;Steinshamn et al, 2006). This improvement may be due to a decrease in CP content of the diet and to an increase of microbial protein synthesis.…”
Section: Strategies To Improve N Use Efficiency In Grazing Systemsmentioning
confidence: 99%